PENGARUH KUALITAS LAYANAN BANK MUAMALAT INDONESIA KANTOR CABANG XXX TERHADAP KEPUASAN NASABAH PRODUK TABUNGAN - Nuzulullaeli , Afiatun; Hakim, Rahmad; Purwadi, Agus (Iqtishodia: Jurnal Ekonomi Syariah, 2020)
Quality of service is the most important aspect in the service industry, including the banking industry. The purpose of this study is to conduct an in-depth analysis related to the effect of service quality on customer satisfaction on savings products at Bank Muamalat Indonesia XXX Branch Office. This type of research is quantitative. Data collection methods in this study were questionnaire and documentation. Data analysis uses validity test, normality test, classic assumption test, and multiple linear analysis test using SPSS. The results found that simultaneous service quality affected the satisfaction of savings customers at Bank Muamalat XXX Branch Office. Partially, variable physical evidence (tangible), reliability (reliability), guarantee (assurance), and empathy (empahty) have a significant effect on customer satisfaction. While responsiveness does not significantly influence customer satisfaction.